Once a day ocular inserts for sustained delivery of levofloxacin: Design, formulation and evaluation - Gevariya, Hitesh; Dharamsi, Abhay; Girhepunje, Kundlik; Pal, Ranju (Asian Journal of Pharmaceutics (AJP), 2014)
Levofloxacin is a fluoroquinolone antibacterial drug effective in the treatment of bacterial conjunctivitis.The objective of the present work was to develop ocular inserts of levofloxacin and evaluate their potential for sustained ocular delivery. Conventional ophthalmic solution shows the poor bioavailability and therapeutic response due to many pre-corneal constraints. These constrains necessitate the controlled and sustained drug delivery to become a standard one in the modern pharmaceutical era. Matrix-type ocular inserts were prepared by the film-casting technique in Teflon-coated Petri dishes and characterized in vitro by drug release studies using a flow-through apparatus that simulated the eye conditions. Nine formulations were developed, which differed in the ratio of polymers polyethylene oxide (PEO), hydroxypropyl cellulose (HPC) and ethyl cellulose (EC). All the formulations were subjected to evaluation of thickness, weight variation, folding endurance and drug content uniformity and in vitro release study. On the basis of in vitro drug release studies, the formulation with PEO/EC (F9) was found to be better than the other formulations (release of 101.35% within 24 hrs) and it was selected as an optimized formulation, which was further subjected to in vivo studies and ageing studies. The in vitro result revealed that formulation F9 followed a perfect zero-order kinetics release (n 5 1.03) and the rest of the formulations released the drug by super case II kinetics (n . 1). It was also observed that increasing the proportion of PEO and HPC to EC increases the rate of release of Levofloxacin. On the basis of in vitro and in vivo correlation stability studies, it can be concluded that this ocular inserts formulation can be a promising once-a-day controlled release formulation.